(untitled) (Stamford Journal of Pharmaceutical Sciences, 2010)
Commercially available twenty national and four multinational brands of Amoxicillin Trihydrate capsules were studied in water for 60 minutes using USP reference dissolution apparatus. All, except two national brands (Code: NB-8 and NB-15); complied with the USP in vitro dissolution specification for drug release (not less than 80% of the labelled amount of amoxicillin trihydrate should be dissolved in 60 minutes). Drug releases from those two brands were 75% and 67% respectively within the specified time period. Key words: In vitro Dissolution; Market preparations; Amoxicillin Trihydrate; Capsule; National Brand; Multinational Brand. DOI: 10.3329/sjps.v2i2.5827 Stamford Journal of Pharmaceutical Sciences Vol.2(2) 2009: 72-75